Methodological Approaches to Managing Business Processes in Pharmacies Using Information Technologies - Georgievna Sboeva, Sanna; Anatolievich Krivosheev, Sergey; Aleksandrovna Klyuyeva, Yulia (International Journal of Engineering and Technology, 2018)
The authors substantiate the need to develop a scientific and methodical approach to modernizing business processes of a pharmacy using information technologies. IK FARM LLC pharmacy has been chosen as a model object of the study. The IDEF0 (Integrated Definition Function Modeling) method adopted as a state standard in the US and recommendations of the State Standard of Russia R 50.1.028-2001 have been used for the analysis, systematization and reorganization of business processes. The article offers methodology for optimizing the pharmacyâ€™s activities, which includes the building of two models for managing business processes â€“ before and after modernization (AS-IS and AS-WILL). The structure of the AS-WILL model includes new functions: â€œPlan the pharmacyâ€™s activitiesâ€ (set the goals and objectives of the organization, plan target sales for the next period) and â€œMonitor the pharmacyâ€™s activitiesâ€ (control the compliance with the rules of drugsâ€™ storage and layout, sanitary regime, and rules of property operation). The complex automation of the pharmacy's trading activities ensures these functions through the Magister software. Estimated efficiency of business processesâ€™ modernization based on the net present value has indicated that automation of processes will increase net unreduced profit.Â Â Â